A Brief Discussion About Measuring Child Molester Cognition With the Sex With Children Scale. (17th December 2014) - Walton, Jamie; Duff, Simon; Chou, Shihning
Abstract : This article reviews the Sex with Children (SWCH) scale and compares its psychometric properties to alternative measures in the field. Examination of the scale indicates that it is one of several instruments which do not proportionally tap into all implicit theory schemas that have been proposed in the literature. This does not help clinicians who aim to target pro‐offending schema since the scale appears to neglect certain types of beliefs that are considered to be important in the investigation of child molester cognition. Similar to many other instruments in the field, the SWCH scale is unlikely to identify offenders who outwardly endorse child abuse items, and its discriminant validity may be better viewed as a capacity to differentiate those who disagree less from those who disagree more. The scale possesses excellent reliability properties compared to other instruments. However, recently reported area under the curve calculations indicate that the scale's predictive power for sexual and violent reconviction is no better than chance. It would be useful to develop the SWCH scale so that it does not under‐represent important types of pro‐offending schema. Copyright © 2014 John Wiley & Sons, Ltd. 'One of several instruments which do not proportionally tap into all implicit theory schemas' Key Practitioner Messages: The SWCH scale has demonstrated excellent reliability properties. The SWCH subscales represent two sexual schemas indicating that the SWCH scale is one of several measures in which nonsexual schemas are under‐represented. Mean scores are low for child molesters indicating that respondents do not often endorse child abuse items outright. It is difficult for clinicians to determine if low endorsement indicates little or no pro‐offending beliefs, post hoc neutralisations or dishonest responding. 'The SWCH scale has demonstrated excellent reliability properties'